Mysterious Cyanosis: A PBL Case on Methemoglobinemia - Luan Lawson; Richard Stair (Association of American Medical Colleges, 2015)
Abstract This problem-based learning (PBL) case is designed for second-year medical students and focuses on the discussion of the presentation of a patient with methemoglobinemia and the underlying processes of hemoglobin and oxygen transport. This PBL case is the re-creation of an emergency department case for an incarcerated patient presenting with dizziness, headache, and cyanosis caused by methemoglobinemia. In addition, the patient has a history of HIV and is on medications for pneumocystis jiroveci pneumonia prophylaxis that serve as the etiology for acquired methemoglobinemia. The case was designed to focus on the considerations of caring for incarcerated patients, hemoglobin transport and impact on the oxygen dissociation curve, and considerations for caring for a patient with HIV. It provides an opportunity for medical students to increase their knowledge and retention about methemoglobinemia and hemoglobin-oxygen transport. More importantly, students are afforded the opportunity to independently and actively learn, through applied cases, the importance of clinical decision-making and evidence-based medicine. This resource is a component of a Foundations in Medicine course designed to help students develop critical thinking skills and evidence-based medicine research skills. We utilized this case with 80 M2 second-semester students during a required PBL course. The case contains actual radiographs, EKG's, CT's, and laboratory data to ensure maximum reality for the students. During our implementation of this case, we found the majority of errors occurred as a result of the failure to recognize methemoglobinemia as a potential etiology for the patient's symptoms. We found many students were focused on the details of the case and needed prompting to focus on the larger picture of the patient's clinical presentation. In implementation, this case required more facilitator input to keep student's moving forward and greater utilization of select prompting questions. Facilitators should also be encouraged to maintain focus on the patient's clinical symptoms and clinical decision-making instead of focusing on the interpretation of radiographic data and EKGs. This case received very good feedback from both faculty and students that the case encouraged them to consider both the social impact on medical conditions as well as medication-induced clinical conditions.